How potassium came to be the dominant biological cation : of metabolism, chemiosmosis, and cation selectivity since the beginnings of life - Korolev, Nikolay (2022)
In the cytoplasm of practically all living cells, potassium is the major cation while sodium dominates in the media (seawater, extracellular fluids). Both prokaryotes and eukaryotes have elaborate mechanisms and spend significant energy to maintain this asymmetric K+ /Na+ distribution. This essay proposes an original line of evidence to explain how bacteria selected potassium at the very beginning of the evolutionary process and why it remains essential for eukaryotes.